Analisis Jaringan Komunikasi Tagar #Prayforkanjuruhan Di Media Sosial Twitter - Aryanto, Dhanu; Nugroho, Catur (eProceedings of Management, 2024)
This research focuses on communication network analysis methods that discuss the relationships in communicationnetworks on the hashtag #PrayForKanjuruhan on Twitter social media. This study aimed to find out the pattern ofcommunication networks, the role of actors in the network, and the critical actors in the communication network withthe hashtag #PrayForKanjuruhan for 1 October 3 30 November 2022. This research uses a qualitative method witha descriptive communication network analysis approach. Researchers chose four main actors in disseminatinginformation related to the keyword or #PrayForKanjuruhan hashtag, namely @panditfootball, @detikcom,@VICE_ID, @NarasiNewsroom. The results of the study reveal that each actor has a wheel network pattern; for rolesthat are calculated through Degree Centrality, Betweenness Centrality, Closeness Centrality, Eigenvector Centrality,the actor who has the most dominant role, and the critical actor from the network, namely @panditfootball with thehighest centrality value among the three actors but has the lowest density of 0.001. Keywords-communication network analysis, #prayforkanjuruhan, twitter, relation, actor.